Academic writing practices in a psychology degree in the distance learning modality (Prácticas de escritura académica en el pregrado de psicología en modalidad a distancia). Issue 1 (2nd January 2023) - Villabona, Lady-Yohanna; Villalón, Ruth
ABSTRACT: University writing practices have primarily been researched at universities with face-to-face classes. The purpose of this study is to describe the writing practices in an undergraduate psychology programme taught in the distance-learning modality based on the vision of both students and instructors. To do so, a survey was administered that inquired into aspects like the presence of writing in the curriculum, the type of feedback provided and received and the genres that are written and read. The data reveal that there is not much difference with the face-to-face learning environment, as writing practices were found with very few spaces of verbal interaction on what has been read or written, a stronger emphasis on the written product than on the composition process and the predominance of note-taking as the consequence of a monologic teaching style. To transform these practices, academic literacy processes that promote the epistemic use of writing and allow for Legitimate Peripheral Participation (LPP) are proposed.